Faithfulness and understanding. From the Millennium Bible (1965) to the Pauline Bible (2008) - Matuszczyk-Podgórska, Bożena (The Bible as a meeting place for Christian denominations, 2022)
This paper attempts to characterize the language of the latest Catholic translation of the Holy Scriptures, i.e. The Bible edited by the Society of Saint Paul (2008). The translation strategies adopted by the translators are discussed in respect of: 1) the tradition of faithful philological translation and 2) the translation of Polish biblical style. The aim is to show the extent to which the translators managed to fulfill two postulates that are difficult to reconcile: faithfulness of translation and comprehensibility of language. The solutions adopted in the Bible edited by the Society of Saint Paul are confronted with the Millennium Bible (1965). In the Millennium Bible the postulate of faithfulness is often fulfilled at the expense of comprehensibility, while in the Bible edited by the Society of Saint Paul both postulates are usually (but not without exceptions) reconciled.